Primary care physician insights into a typology of the complex patient in primary care - Loeb, Danielle F; Binswanger, Ingrid A; Candrian, Carey; Bayliss, Elizabeth A (Annals of family medicine, 2015)
Primary care physicians play unique roles caring for complex patients, often acting as the hub for their care and coordinating care among specialists. To inform the clinical application of new models of care for complex patients, we sought to understand how these physicians conceptualize patient complexity and to develop a corresponding typology. We conducted qualitative in-depth interviews with internal medicine primary care physicians from 5 clinics associated with a university hospital and a community health hospital. We used systematic nonprobabilistic sampling to achieve an even distribution of sex, years in practice, and type of practice. The interviews were analyzed using a team-based participatory general inductive approach. The 15 physicians in this study endorsed a multidimensional concept of patient complexity. The physicians perceived patients to be complex if they had an exacerbating factor-a medical illness, mental illness, socioeconomic challenge, or behavior or trait (or some combination thereof)-that complicated care for chronic medical illnesses. This perspective of primary care physicians caring for complex patients can help refine models of complexity to design interventions or models of care that improve outcomes for these patients.